Interfacial Microstructure and Cladding Corrosion Resistance of Stainless Steel/Carbon Steel Clad Plates at Different Rolling Reduction Ratios - Jie Chen; Yixin Zhu; Xia Chen; Xiaoli Ma; Bin Chen (Metals)
Optical microscope (OM), energy dispersive spectrometer (EDS), electron backscatter diffractometer (EBSD), electrochemical test, and transmission electron microscope (TEM) were employed to conduct interface microstructure observation and cladding corrosion resistance analysis on 304 SS/CS clad plates that have four different reduction ratios. The increase in rolling reduction ratio leads to larger grain size, gradually refined microstructure, and a decreased thickness of the interfacial martensite area. As the concentration disparity of the C element between carbon steel (CS) and 304 stainless steel (SS) is small, no evident carburization layer or decarburization layer can be detected. The ferrite microstructure on the CS side has greater stress distribution and greater local orientation deviation, and deformed grains are dominant. Austenite undergoes strain-induced martensitic transformation with the transformation mechanism of γ→twinning→a’-martensite. The martensite microstructure within the interface region grows in the direction of the interior of austenite grains. The reduction ratio increases sharply, leading to an increase in dislocation density, which promotes the nucleation, growth, and precipitation of carbides and seriously reduces the corrosion resistance of the cladding. Subsequently, the reduction ratio keeps on increasing. However, the degree of change in the reduction ratio diminishes. High temperature promotes the dissolution of carbides and improves the corrosion resistance. From this, it can be understood that by applying the process conditions of raising the reduction ratio and keeping a high temperature at the carbide dissolution temperature, a clad plate that has excellent interface bonding and remarkable corrosion resistance can be acquired.